2019
DOI: 10.1080/07391102.2018.1534700
|View full text |Cite
|
Sign up to set email alerts
|

Tris-chelated complexes of nickel(II) with bipyridine derivatives: DNA binding and cleavage, BSA binding, molecular docking, and cytotoxicity

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
1
12
0
1
Order By: Relevance
“…Here, the affinity of BSA towards our complexes was investigated by tracking the changes in the electronic absorption spectra of the complexes. [ 42,43 ] Protein titration plots of compounds 1–3 are shown in Figure 6. The spectral changes upon the addition of BSA to the solutions of the complexes were tracked at 266, 264 and 288 nm for 1 – 3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the affinity of BSA towards our complexes was investigated by tracking the changes in the electronic absorption spectra of the complexes. [ 42,43 ] Protein titration plots of compounds 1–3 are shown in Figure 6. The spectral changes upon the addition of BSA to the solutions of the complexes were tracked at 266, 264 and 288 nm for 1 – 3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our investigations to provide further insights into the therapeutic properties of metal-based compounds [108] , [109] , [110] , [111] , [112] , [113] , [114] , [115] , [116] , [117] , [118] , we herein highlight the recent progress conducted on the potential therapeutic applications of AMSs. This review begins with mechanistic concepts of AMS-catalyzed nucleic acids cleavage ( Section 2 ), followed by model substrates and instrumentations employed in cleavage studies ( Section 3 ).…”
Section: Introductionmentioning
confidence: 94%
“…These inheritable small DNA molecules are routinely found in prokaryotes and typically carry genes of secondary metabolism. Plasmids have a wide range of lengths, roughly from 1 to 100 kbp [96] , [99] , [108] , [115] .…”
Section: Models Substrates and Instrumentations Employedmentioning
confidence: 99%
“…However, we have shown that diketone complexes are selective (selectivity index > 3) and that phenanthroline and its derivatives are not selective or active for some cell lines [5,8]. As to the MCF-7 cells, the complexes reported here possess similar or higher activity when compared to other nickel complexes already described [26][27][28][29].…”
Section: In Vitro Anti-tumoral Activitymentioning
confidence: 62%
“…VENKATA RAMANA REDDY, 2018;ANJOMSHOA et al, 2019;DEVI et al, 2019;. (LI et al, 2014;KAZEMI et al, 2015;BARRA et al, 2016) REHMAN et al, 2015).…”
Section: Atividade Antitumoral In Vitro Dos Complexos De Ni II E Cu Iiunclassified